Motivational incentives and methylphenidate enhance electrophysiological correlates of error monitoring in children with attention deficit/hyperactivity disorder - Groom, Madeleine J.; Liddle, Elizabeth B.; Scerif, Gaia; Liddle, Peter F.; Batty, Martin J.; Liotti, Mario; Hollis, Chris (Wiley, 2013)
Background Children with attention deficit hyperactivity disorder (ADHD) are characterised by developmentally inappropriate levels of hyperactivity, impulsivity and/or inattention and are particularly impaired when performing tasks that require a high level of cognitive control. Methylphenidate (MPH) and motivational incentives may help improve cognitive control by enhancing the ability to monitor response accuracy and regulate performance accordingly.